LEARNING CYCLE UNTUK MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR IPA DI MTsN 1 BANTUL - ASIH BUDIATI (SCIENCE : Jurnal Inovasi Pendidikan Matematika dan IPA, 2022)
This study is intended to determine the effect of applying the Learning Cycle learning model in overcoming problems in the classroom in the form of low activity and science learning outcomes at MTsN 1 Bantul for the 2021-2022 academic year. This research was carried out in the odd semester of the 2021-2022 academic year covering two cycles of learning activities consisting of six meetings, by applying the Learning Cycle learning model. The subjects of this study were students of class IX D at MTsN 1 Bantul, totaling 16 with 7 students and 9 students (limited PTM). The implementation of the Learning Cycle learning model is learning that has the syntax/stages of Angagement, Exploration, Explanation, Elaboration, and Evaluation at the core of learning. The data collection methods used were observation, documentation, and learning outcomes tests. The data obtained in the field were analyzed using qualitative analysis techniques. In carrying out research using the Learning Cycle learning model in science learning in class IXD MTsN 1 Bantul for the 2021-2022 school year, the results show that the Learning Cycle model has a positive effect on student activity and science learning outcomes. This is indicated by the increased activeness of students during learning at all stages of the learning cycle 65.8% in the first cycle and increased to 81.7% at the end of the second cycle. Likewise with student learning outcomes, namely the highest score of 80 in the first cycle to 85 in the second cycle, the lowest score of 60 in the first cycle to 65 in the second cycle, and the average value from 66.56 in the first cycle to 77.19 in the second cycle. . The number of students who reached the KKM were 3 students in the first cycle to 13 students in the second cycle. The data has met the success criteria, so it can be said that the Learning Cycle can increase the activeness and learning outcomes of science at MTsN 1 Bantul for the academic year 2021-2022. ABSTRAKPenelitian ini dimaksudkan untuk mengetahui pengaruh penerapan model pembelajaran Learing Cycle dalam mengatasi permasalahan di kelas berupa masih rendahnya aktifitas dan hasil belajar IPA di MTsN 1 Bantul tahun pelajaran 2021-2022. Penelitian ini dilaksanakan pada semester gasal tahun pelajaran 2021-2022 meliputi kegiatan pembelajaran sebanyak dua siklus yang terdiri dari enam pertemuan, dengan menerapkan model pembelajaran Learning Cycle. Subyek pembelajaran ini adalah siswa kelas IX D di MTsN 1 Bantul yang berjumlah 16 dengan 7 siswi dan 9 siswa (PTM terbatas). Pelaksanaan model pembelajaran Learning Cycle yaitu pembelajaran yang mempunyai sintak/tahap Angagement, Exploration, Explanation, Elaboration, dan Evaluation di inti pembelajaran. Metode pengumpulan data yang digunakan adalah observasi, dokumentasi, dan tes hasil belajar. Data yang diperoleh di lapangan dianalisis menggunakan teknik analisis kualitatif. Dalam pelaksanaan penelitian dengan penerapan model pembelajaran Learning Cycle dalam belajar IPA di kelas IXD MTsN 1 Bantul tahun pelajaran 2021-2022 diperoleh hasil bahwa model Learning Cycle berpengaruh positif terhadap keaktifan dan hasil belajar IPA siswa. Hal tersebut ditunjukkan dengan meningkatnya keaktifan siswa selama pembelajaran pada semua tahap learning cycle 65,8 % pada siklus I dan meningkat menjadi 81,7% pada akhir siklus II. Demikian pula dengan hasil belajar siswa yakni nilai tertinggi 80 di siklus I menjadi 85 di siklus II, nilai terendah 60 pada siklus I menjadi 65 pada siklus II, serta nilai rata-rata dari 66,56 pada siklus I menjadi 77,19 pada siklus II. Jumlah siswa yang mencapai KKM ada 3 siswa di siklus I menjadi 13 siswa di siklus II. Data tersebut telah memenuhi kriteria keberhasilan sehingga dapat dikatakan bahwa Learning Cycle dapat meningkatkan keaktifan dan hasil belajar IPA di MTsN 1 Bantul tahun pelajaran 2021-2022.